Interviewer training module system best interviewing skills and strategies to hire the right information technology worker - Kamini, Manikam. (Universiti Malaysia Sarawak, UNIMAS, 2007)
The progression of Information Communication Technology in Malaysia ever since the conceptualization of Multimedia Super Corridor (MSC) has not only accelerated growth and sustainable development amongst home-grown companies but has also made a boom in the IT job market. There are superfluous of IT job seekers in the market but only few among them have the exact competency for the required job. Hiring the right person among a pool of job applicants is a challenging task and therein lies the requirement for best skills and strategies that are imperative to be mastered by HR Managers. This study examines the current malpractice in IT Job interview in which HR Managers ask questions that are not job-related thus hiring incompetent candidates that contribute low performance in organizations. The purpose of this study is to develop an instructional material in the form of courseware that would provide a computer- based training for HR Managers on best interviewing skills and strategies to hire the right IT worker for both small industries and corporations in Malaysia. This Interviewer training module system is developed using the ADDIE Instructional System Design (ISD) technique methodology which involves a systematic approach to Analyse, Design, Develop, Implement and Evaluate. The courseware is evaluated among 25 users from 10 companies in Kuching and Kuala Lumpur .The results verifythat this Interviewer training module system is very effective, efficient and applicable in the real working environment.